Data Management for mobile applications dependent on geo-located data - Santos, Nuno M. (2023)
This work was partially supported by EU Horizon Europe under Grant Agreement no. 101093006 (TaRDIS). Dataset expansion was possible by API access to OpenRouteService from HeiGIT gGmbH. Publisher Copyright: © 2023 Owner/Author(s).